Structures of prokaryotic ubiquitin-like protein Pup in complex with depupylase Dop reveal the mechanism of catalytic phosphate formation - Hengjun Cui (Nature Portfolio, 2021)
Pupylation is a bacterial post-translational protein modification, where the small ubiquitin-like protein Pup is covalently attached to lysine side chains of target proteins, which is a reversible process and depupylation is catalysed by the depupylase enzyme, Dop. Here, the authors present crystal structures of Dop in different functional states, which together with biochemical experiments provide insights into the catalytic mechanism of this enzyme.